Thermo-Mechanical Analysis and Durability Optimization of the Piston - Fattah Agha, Mothanna Taha Mohammed (Indonesian Journal Publisher, 2025)
This study evaluated both the thermal and mechanical performance of an internal combustion engine piston in different operating conditions. A comprehensive thermo-mechanical analysis was performed to evaluate temperature distribution, heat transfer behavior, pressure accumulation and visco-plastic stress in various parts of the piston. The results show that there is considerable thermal influence on the flame face, first ring groove and crown underside of the oil area for different operating conditions, i.e., rated vs. idle conditions. Thermal and visco-plastic strain concentrations are illustrated as being a result of cyclically increasing temperatures in the stabilized 5th cycle examination; however, visco-plastic stresses remained well below maximum allowable values. Additionally, the TMF-based life prediction indicated that the piston design is capable of withstanding more than 3000 cycles and will not fail with reasonable probability. The study also indicates the need for understanding thermal boundary conditions within ring grooves and how heat transfer coefficient (HTC) values may be used to regulate piston surface temperature, which will lead to better engine reliability and efficiency by providing an optimized material selection and thermal management strategy for the piston.